A BRAKE PRESSURE MODULATOR, PNEUMATIC BRAKE SYSTEM AND VEHICLE - RIEDIGER-JANISCH, Karl-Heinz (2022)
The present invention relates to a brake pressure modulator (110, 110a, 110b, 110c, 106), comprising: - a relay valve (202) for controlling a supply of pressurized air from a primary source (II) to at least one brake actuator (112a, 112b); - a first valve sub-unit (204) configured to be electronically actuated, wherein the first valve sub-unit (204) is configured to receive a primary control pressure from the primary source (II) intended for opening the relay valve (202); and - a second valve unit (206) configured to at least receive a secondary control pressure from a secondary source ('BST') and at least part of the primary control pressure from the primary source (II) and to transmit either the primary control pressure or the secondary control pressure to the relay valve (202), wherein, when the secondary control pressure is transmitted to the relay valve (202), the primary control pressure from the primary source (II) is disconnected, and/or when the primary control pressure is transmitted to the relay valve (202), the secondary control pressure from the secondary source (BST) is disconnected. According to the invention the second valve unit (206) is a mechanically operable valve, in form of a pneumatically controlled valve (206D, 206A, 206B, 206C) having a valve casing (304), the valve casing (304) comprising: - a pressurized guiding sleeve (304.4) providing a valve chamber (305) configured to axially guide a pressure pickup piston or the like spool (320) adapted for pneumatic actuation thereof, in particular adapted for mere pneumatic actuation thereof, and - a coil casing (304.5) configured to provide a coil chamber (306) peripheral next to the pressurized guiding sleeve (304.4), wherein the valve chamber (305) is free of a spring (321) and the coil chamber (306) is free of a coil or the like solenoid (311), such that the spool (320) is actuable pneumatically only, in particular wherein the spool (320) is subject to a pneumatic force only due to pneumatic pressure in the valve chamber (305). La présente invention concerne un modulateur de pression de freinage (110, 110a, 110b, 110c, 106) comprenant : - une soupape de relais (202) pour commander une alimentation en air sous pression d'une source primaire (II) à au moins un actionneur de frein (112a, 112b) ; - une première sous-unité de soupape (204) conçue pour être actionnée électroniquement, la première sous-unité de soupape (204) étant conçue pour recevoir une pression de commande primaire provenant de la source primaire (II) destinée à ouvrir la soupape de relais (202) ; et - une seconde unité de soupape (206) conçue pour au moins recevoir une pression de commande secondaire provenant d'une source secondaire (« BST ») et au moins une partie de la pression de commande primaire provenant de la source primaire (II) et pour transmettre soit la pression de commande primaire soit la pression de commande secondaire à la soupape de relais (202), et lorsque la pression de commande secondaire est transmise à la soupape de relais (202), la pression de commande primaire provenant de la source primaire (II) étant déconnectée, et/ou lorsque la pression de commande primaire est transmise à la soupape de relais (202), la pression de commande secondaire provenant de la source secondaire (BST) étant déconnectée. Selon l'invention, la seconde unité de soupape (206) est une soupape à commande mécanique, sous la forme d'une soupape à commande pneumatique (206D, 206A, 206B, 206C) ayant un boîtier de soupape (304), le boîtier de soupape (304) comprenant : - un manchon de guidage sous pression (304.4) fournissant une chambre de soupape (305) configuré pour guider axialement un piston de capture de pression ou un corps similaire (320) conçu pour un actionnement pneumatique de celui-ci, en particulier conçu pour un simple actionnement pneumatique de celui-ci, et - un boîtier de bobine (304.5) configuré pour fournir une chambre de bobine (306) périphérique à côté du manchon de guidage sous pression (304.4), la chambre de soupape (305) étant dépourvue d'un ressort (321) et la chambre de bobine (306) étant dépourvue d'une bobine ou d'un solénoïde similaire (311) de sorte que la bobine (320) puisse être actionnée de manière pneumatique uniquement, en particulier lorsque la bobine (320) est soumise à une force pneumatique uniquement en raison de la pression pneumatique dans la chambre de soupape (305).